E a vida continua...: o processo de luto dos pais após o suicídio de um filho - Silva, Daniela Reis e (2009)
Suicide is a complex behavior and is considered as a public health problem. Little attention has been given to the surviving family members. The present research deals with the process of parental bereavement due to a child suicide. The process gathers two variable of potential risk for the development of complicated mourning: the loss of a child and the kind of death involving suicide. The research analyses matters related to the suicide of a child by means of a case study, which is based on a qualitative method, involving a mother who lost her son by suicide one year and three months before the study. A semi-structured interview and the construction of a genogram are used as tools. The thematic analysis reveals a singular bereavement process involving trauma and grief. It presents the son characteristics, the illness history, the suicide, the shock, the guilt, the paralysis, longing feelings, sadness, the ups and downs, the health and the resiliency among other emerging aspects, which seem to be mixed in the participant s verbalization influencing in a recurrent way the mourning process. The author draws the conclusion that religiosity, professional support, social support, art, meaning constructions, the way of sharing among other resources of confrontation can contribute positively, although in a short period of time, for a change in the future expectation. The author considers that the achieved information is only the beginning of recognition of the importance of not labeling negatively the survival family members over suicide, besides the possibility of breaking silence and prejudice involved in it so that they can receive the right support